PENGARUH INTENSITAS TERPAAN PROMOSI PENJUALAN BLIBLI.COM DI TELEVISI DAN TINGKAT KEPERCAYAAN PADA PRODUK TERHADAP TINGKAT MINAT MEMBELI PRODUK PADA BLIBLI.COM - Neysa Harwina Putri; Djoko Setyabudi; Sunarto Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Along with the development of the times, communication media are also experienced rapid development. This increased modern communication media is also used for business activities, one of which is using television media. This research uses marketing communication theory. Exposure to sales promotions on television is carried out in order to influence the buying interest of the audience. One of the companies that advertised on television is Blibli.com. Blibli.com is a well-known e-commerce platform in Indonesia that features well-known artists in advertisements on television. Blibli.com also made efforts to increase trust. However, there has been a decrease in the number of visits to the Blibli.com website. This study aims to analyze the effect of exposure to sales promotions and the level of trust on product purchase intention at Blibli.com. This study uses a quantitative method with a population of Blibli users who have seen Blibli advertisements on television and live in Semarang with a sample of 100 people. The sampling technique used in this research is purposive sampling. The data obtained came from filling out online questionnaires by respondents. The data analysis method in this study used multiple linear regression using the SPSS program. The results of this study indicated that exposure to sales promotions and level of trust have a significant positive effect on product purchase intention at Blibli.com. The implications of this research provides input for Blibli.com in increasing and maintaining exposure to sales promotions and the level of trust to increase product purchase intention at Blibli.com